(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2011)
A serrated tooth from the Coniacian-Santonian (Upper Cretaceous) Polazzo fossil site (Karst, NE Italy) is the first record of a notosuchian crocodyliform from Italy. Although it shares synapomorphies with teeth referred to the European genus Doratodon and with the Gondwanan genus Araripesuchus, it is distinct in the unusual combination of features, suggesting the presence of a yet unreported notosuchian taxon in the Adriatic-Dinaric Carbonate Platform located in the Tethys between the Afroarabian continent and the North European landmass during Late Cretaceous times. Notosuchians were typically terrestrial crocodyliforms, supporting the presence of emergent areas on the carbonate platform.